Metabolic and molecular regulation in skeletal muscle dysfunction and regeneration - Jin, Jong Beom; Robinson, Angelique; Soukup, Tori; Black, Ember; Abit, André; Hammer, Shane M.; Han, Anna; Lucas, Edralin; Kim, Yoo; Bae, Jiyoung (Frontiers in Cell and Developmental Biology, 2025)
Skeletal muscle is an important organ in the human body for maintaining overall strength and mobility. Skeletal muscle has the capability of self-regeneration, which can be achieved by utilizing specific energy pathways. Therefore, understanding the energy metabolism of skeletal muscle is essential to exploring its regenerative mechanisms. This review addresses the current progress in understanding the essential role of metabolic pathways in skeletal muscle function, regeneration, and muscle dysfunction as it relates to diseases such as type 2 diabetes mellitus (T2DM), obesity, and aging (sarcopenia). Furthermore, we explore the fundamental metabolisms of skeletal muscle while considering not only disease progression but also therapeutic strategies. Experimental models (in vivo and in vitro) and other signaling pathways are additionally discussed while proposing that the association between energy metabolism markers and metabolic diseases in skeletal muscle could provide innovative implications. Finally, the need for developing human-relevant models to study muscle regeneration is emphasized as most current findings are derived from in vivo and in vitro models.